The Effect of Special Olympics Programs on Down Syndrome People\'s Self-Efficacy - Maryam Momeni; Hamid Reza Taheri (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: Literature survey has shown that participation in social programs can promote the mental and social health among intellectually disabled individuals. One of these programs is the Special Olympics (SO) and the programs related to it. The aim of this study was to investigate the effect of SO programs on self-efficacy among Iranian Special Olympians with Down Syndrome (DS). Materials & Methods: In this quasi-experimental research, forty DS members of Iran's SO national team were selected as the intervention group and 37 DS non-athletes were selected as the control group. The SO group participated in 9 months of SO specific sport programs. The "Wheeler and Ladd's Children's Self-Efficacy for Peer Interactions Scale" was used to collect data from the two groups before and after the 9-month long athletic programs. Data were analyzed by kolmogroff-Smirnoff, paired T and independent T tests. Results: The results showed that SO programs had significant effects on the self- efficacy of the experimental group. The SO athletes were significantly (P&le0.001) better than the control group in all sub-scales of self-efficacy. Conclusion: It seems that participation in social-sport aspects of the Special Olympics programs can promote self-efficacy among this population. Generalizing such programs for DS people can help them show their abilities and provide them with self-efficacy which is necessary for living independently.